From pregnancy to plate: understanding barriers and facilitators of fish consumption during complementary feeding - Metin Yigit; Beytullah Santaflioglu; Enes Kaan Kilic; Kaan Celebier; Furkan Kalayci (BMC Pediatrics)
Abstract Background Fish is a crucial source of nutrients for early childhood development, yet various cultural and informational barriers hinder its adequate consumption. This study aimed to investigate the factors affecting fish consumption during complementary feeding and to examine the role of maternal dietary habits, parental attitudes and health guidance in shaping children’s fish consumption practices. Method A descriptive cross-sectional study using a 35-item questionnaire was conducted to assess demographic characteristics, fish consumption practices during complementary feeding, and the role of healthcare guidance. Results Parental education level and healthcare guidance were both significantly associated with higher frequency and earlier introduction of fish in children’s diets; however, maternal fish consumption during pregnancy showed the strongest impact on these outcomes. Children of mothers who consumed fish weekly during pregnancy were 14.9 times more likely to consume fish frequently, and families receiving healthcare guidance were 2.5 times more likely to introduce fish during complementary feeding. Key barriers included fears of fishbones, allergies, and heavy metal contamination. Despite these challenges, healthcare guidance on fish consumption was significantly associated with higher intake and earlier introduction. Conclusion Addressing misconceptions, enhancing healthcare guidance, and promoting educational interventions are critical to improving fish consumption during complementary feeding. These findings provide a basis for strategies to optimize early childhood nutrition and promote healthier dietary habits.